Climate smart land configurations and cropping systems diversification sustaining soil–water–carbon synergy and resource use efficiency - Yogeshwar Singh; Shiv Vendra Singh; Susheel Kumar Singh; Sandeep Upadhyay; Rajeev Nandan; Anil Kumar Rai; Tony Manoj K. Nandipamu; Ram Kewal Singh; Sushil Kumar Chaturvedi; Ashok Kumar Singh (Resources, Environment and Sustainability)
Erratic rainfall, water availability and soil health in drought-prone regions require climate-resilient strategies for improving water management, soil carbon-nutrient cycling, and water and carbon footprint mitigation. Present investigation was designed and executed with four in-situ rainwater harvesting methods viz., Conventional Tillage (CT), Residue Mulch (RM), Broad Bed and Furrow (BBF) and Ridge and Furrow (R&F) and promising cropping systems of the region viz., Groundnut–wheat (GN-W), Sorghum–Chickpea (S-CP) and Maize–Mustard–Sesbania (M-M-S). Residue recycling (RM) enhanced SOC by 16%–19% and N, P2O5, and K2O by 5%–30%. The RM significantly improved the moisture availability during dry periods at vegetative and reproductive stages, which resulted in improving the soil chemistry and water regimes, thus improving better photosynthate partitioning, pigmentation, leaf turgidity, and system productivity. The carbon footprint (CF) trend among establishment methods was CT>BBF>RM>R&F while it was 54.7, 29.5 and 29.7 % higher over under CT over rest. The CF under M-M-S significantly enhance the carbon sequestration across the establishment methods being maximum under RM (7.68 Mg CO2-Ce ha −1) which was increased by 29 % in SOC stock over initial value. Combinedly, M-M-S in R&F can address the issue of both water scarcity during dry spells and water logging during heavy rains however, M-M-S and GN-W with RM can be promising to reduce water and carbon footprint with high SOC stock. Residue recycling (RM) can assure the higher soil moisture availability during dry spells, better WF, CF and MEY, moreover, legumes inclusion is excellent in enhancing resource use efficiency and ecological sustainability.